Current practices and perspectives for metadata on web ontologies and rules. (25th October 2012) - Tejo-Alonso, Carlos; Berrueta, Diego; Polo, Luis; Fernández, Sergio
The Semantic Web contains a number of knowledge artifacts, including OWL ontologies, RIF rule sets and Resource Description Framework data sets. Effective exchange and management of these artifacts demands the use of metadata and prompt availability of accurate reference documentation. In this paper, we analyse the current practices in metadata usage for OWL ontologies and we propose a vocabulary for annotating RIF rules. We also introduce a software tool -Parrot- that exploits these annotations and produces reference documentation for combinations of ontologies and rules.